Optimization of volume-limited thermal energy storage in non-continuous processes. (15th July 2020) - Stampfli, Jan A.; Lucas, Edward J.; Ong, Benjamin H.Y.; Olsen, Donald G.; Krummenacher, Pierre; Wellig, Beat
Abstract: Due to the nature of non-continuous processes, heat recovery through direct heat integration is limited. Thermal energy storage (TES) is usually employed for indirect heat transfer, provided excess heat sources and sinks are available. Such processes may have brief peaks in energy demand, necessitating large TES. However, practical space constraints often limit maximal storage volumes, restricting the potential for heat recovery. This paper aims to develop a linear programming optimization model to determine the storage integration solutions which maximize heat recovery per batch for volume-limited sensible stratified storage. Indirect source and sink profiles are used to determine maximum process heat recovery and subsequently the initial TES capacity. The results produce a process-specific capacity limitation chart of batch-wise maximal heat recovery, allowing generation of optimal storage loading and unloading profiles. The optimization model was applied to two case studies. The resulting capacity limitation chart shows that a stratified storage, with a volume of total 96 m 3 is needed to achieve 100 % of the trageted direct and indirect heat recovery. Approximately 60 % heat recovery can already be achieved by using only a 4 m 3 storage. The model is extended to a fixed temperature variable mass storage with multiple VSUs. Graphical abstract: Image 1 Highlights: Developed an optimization model to maximize heat recovery for volume-limited storage. Applied the model to stratified and fixed temperature variable mass storages. Optimized the loading and unloading profiles for maximum heat recovery. Identified critical volumes for storage design.